Helminth parasites of the invasive European brown hare (Lepus europaeus) in Brazil: the first report of Bunostomum trigonocephalum in a hare - Arias-Pacheco, Carmen [UNESP]; Perin, Patricia Parreira [UNESP]; Oliveira, Wilson Junior [UNESP]; de Souza Pollo, Andressa [UNESP]; Benatti, Danise [UNESP]; Mendonça, Talita Oliveira [UNESP]; de Oliveira Andrade, Lívia [UNESP]; Gomes, Jonathan Silvestre [UNESP]; de Oliveira Zolla, Natália [UNESP]; de Moraes Ferreira, Adrian Felipe [UNESP]; dos Santos, Vitória Maximiana Soares [UNESP]; Lux Hoppe, Estevam G. [UNESP] (Springer Nature, 2024)
Invasive alien species have the potential to introduce pathogens of economic and health importance in new environments. In Brazil, parasites from the non-native European brown hare can be a threat to humans, domestic animals, and wildlife. Therefore, we aimed to describe the helminth fauna of the invasive European brown hare in three Brazilian states (São Paulo, Paraná, and Rio Grande do Sul). For this, 90 brown hares were collected and examined for helminths. Helminth specimens recovered were morphologically identified and genetically characterized based on the DNA of male specimens using three genetic regions (28S rDNA, ITS-2, and cox-1 mtDNA). Descriptors of infection were calculated, and statistical analysis was performed. Parasites were found only in the small intestine of 14.4% (13/90) of brown hares and low parasite loads per animal were recorded (range = 1–530). The obtained specimens were morphologically identified as Trichostrongylus colubriformis and Bunostomum trigonocephalum. There was a high level of agreement between phylogenetic analysis and morphology for T. colubriformis. The geographical region was the only significant factor for infection; the State of Rio Grande do Sul had a higher general prevalence, higher T. colubriformis specific prevalence, and higher mean abundance than the other states evaluated. All hares were in a good body condition. To our knowledge, this is a new host record for B. trigonocephalum. This is the first study on the helminthological diversity of European brown hares in Brazil, and our results indicate that their helminth fauna is represented by parasites of domestic ruminants with zoonotic potential.
Keywords: Bunostomum trigonocephalum; Invasive species; Parasite-host relationship; Phylogeny; Trichostrongylus colubriformis